2019
DOI: 10.1038/s41598-018-36271-w
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Interface Energetics for Efficient Charge Separation in Metal Oxide-Polymer Solar Cells

Abstract: Hybrid organic-inorganic heterointerfaces in solar cells suffer from inefficient charge separation yet the origin of performance limitations are widely unknown. In this work, we focus on the role of metal oxide-polymer interface energetics in a charge generation process. For this purpose, we present novel benzothiadiazole based thiophene oligomers that tailor the surface energetics of the inorganic acceptor TiO2 systematically. In a simple bilayer structure with the donor polymer poly(3-hexylthiophene) (P3HT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The detailed synthetic route of oligothiophene phosphonic acids (OT-PAs) is demonstrated in the Supporting Information (SI), based on the previous work. 4 The oligomer phosphonic acids with the diethoxyphosphoryl group (Phos-Ph-(3HT)s) were synthesized by the Suzuki−Miyaura coupling polymerization between the palladium initiator bromo(4-diethoxyphosphoryl-phenyl)(tri-tertbutylphosphine)palladium(II) (Phos-Ph-Pd) and 2-(5-bromo-4-hexylthiophen-2-yl)-4,4,5,5-tetramethyl-1,3,2-dioxaborolane in a Schlenk tube. The oligomers were extracted with dichloromethane and purified in toluene.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The detailed synthetic route of oligothiophene phosphonic acids (OT-PAs) is demonstrated in the Supporting Information (SI), based on the previous work. 4 The oligomer phosphonic acids with the diethoxyphosphoryl group (Phos-Ph-(3HT)s) were synthesized by the Suzuki−Miyaura coupling polymerization between the palladium initiator bromo(4-diethoxyphosphoryl-phenyl)(tri-tertbutylphosphine)palladium(II) (Phos-Ph-Pd) and 2-(5-bromo-4-hexylthiophen-2-yl)-4,4,5,5-tetramethyl-1,3,2-dioxaborolane in a Schlenk tube. The oligomers were extracted with dichloromethane and purified in toluene.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Self-assembled monolayers (SAMs) are broadly utilized as surface modifiers due to the very facile fabrication process, thus exhibiting strong potential in organic electronics, water treatments, and biosensors . In organic thin-film field-effect transistors, SAMs usually serve to modify the interface properties, either between the insulator and the semiconductor or between the electrodes and the gate dielectric. , Since the first study of self-assembled monolayer field-effect transistors (SAMFETs), the molecular design of SAM semiconductors that simultaneously combine a conjugated unit, alkyl chains, and an anchor group within a single molecule has raised notable interest. For instance, a semiconducting SAM with a quarter-thiophene moiety introduced by Mottaghi et al shows the possibility of charge transfer in a densely packed single layer .…”
Section: Introductionmentioning
confidence: 99%
“…However, to use this approximation correctly, and for comparative purposes, particle size distribution must follow a monomodal distribution, with a polydispersity index below 0.3. In addition, to be more sensitive to small numbers of aggregates or dust, such a particle size must preferably be reported as an intensity correlated function of the scattered light rather than by volume or number of particles distribution [ 91 ]. The particle size of formulations, along with the presence of possible aggregates, can also be analyzed with appropriate staining reagents such as uranyl acetate by different microscopic techniques, including transmission electron microscopy (TEM), cryo-TEM, scan electronic microscopy (SEM) or atomic force microscopy (AFM) [ 92 ].…”
Section: Design Of Experimental Conditionsmentioning
confidence: 99%
“…However, the same scheme does not work for ZnO, which the authors ascribe to the more pronounced and unfavorable interface dipole in that case. A different study that employed diethylphosphonate-benzodiathiazole terminated thiophene oligomers of different length highlighted the role of the energetics across the molecularly modified hybrid interface and suggested that both a large energy offset and a suitable energy cascade facilitate exciton dissociation and prevent recombination [422]. Energy transfer from P3HT to a surface-bonded dye, followed by electron injection from the dye into TiO 2 represents an alternative pathway for exciton harvest [423].…”
Section: Organic Interlayersmentioning
confidence: 99%